A qualitative evaluation of the appropriateness, validity, acceptability, feasibility and interpretability of the Bristol Impact of Hypermobility (BIoH) questionnaire. (December 2018) - Manns, Sarah; Cramp, Fiona; Lewis, Rachel; Clark, Emma M.; Palmer, Shea
Abstract: Background: The Bristol Impact of Hypermobility (BIoH) questionnaire is a condition-specific patient-reported outcome measure developed for adults with Joint Hypermobility Syndrome (JHS). It has previously demonstrated strong concurrent validity with the Short-Form 36 health questionnaire and excellent test-retest reliability. Objectives: This study aimed to evaluate its appropriateness, validity, acceptability, feasibility and interpretability. Design: A qualitative evaluation using semi-structured telephone interviews, incorporating a 'think aloud' exercise and additional prompts. Method: Adults with JHS (n = 11) were recruited through a patient organisation and physiotherapists with a professional interest in JHS (n = 9) were recruited through the same organisation and an online professional network. Interviews were transcribed and data synthesised using a framework matrix. Findings: Patients and physiotherapists commented positively on the appropriateness, validity, acceptability and feasibility of the BIoH questionnaire. Physiotherapists assessed the interpretability of the questionnaire and commented that, whilst further information might be captured, the value of that information might be limited. The questionnaire was considered comprehensive with only a very limited number of potential missing areas related to use of hand-held technology, hair washing/drying and intimacy. Interestingly, keyboard use and hair washing were excluded during initial questionnaire development as they were rated as relatively unimportant. Intimacy was not considered a comfortable addition for all participants. Conclusions: Patients and physiotherapists regarded the BIoH questionnaire as a welcome addition to the toolkit available to assess those with JHS. It was broadly accepted as reflecting the experience of people with JHS in sufficient detail to support management. Highlights: The BIoH questionnaire was regarded positively by patients and physiotherapists. It is a welcome addition to the toolkit available to assess those with JHS. It captures the experiences of people with JHS. It does so in sufficient detail to support management.